Open clusters in the Gaia-ESO Survey: tracing the chemical history of the Milky Way thin disk. Issue 67 (17th July 2015) - Magrini, L.; Randich, S.
Abstract : The Gaia-ESO Survey (GES) is a large public spectroscopic survey that aims at observing with FLAMES@VLT the main stellar components of our Galaxy. The study of the population of open clusters is one of the main objectives of GES. We present some results from the first 18 months of observations, among them, a preliminary view of the radial metallicity gradient as traced by open cluster data and a comparison of the chemical patterns of clusters located in different parts of the Galactic disk.